2011
DOI: 10.1108/02640471111156759
|View full text |Cite
|
Sign up to set email alerts
|

An investigation‐based learning model for using digital libraries to support mobile learning activities

Abstract: PurposeThis study proposes a mobile learning model that employs digital libraries to support investigative learning activities. A student‐centered mobile learning activity with self‐guided exploration for physical ecology observation has been conducted to demonstrate the benefits of using digital libraries to support investigation‐based ecology learning activities.Design/methodology/approachAn investigation‐based mobile learning model is proposed and an experiment is designed to show the effectiveness of the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 32 publications
0
24
0
Order By: Relevance
“…However, a large number of responses related to the integration of the technology into teaching and learning. Other studies have explored such integration; for example using digital libraries to support mobile learning activities [31] and effects of an inquiry-based mobile learning model on the cognitive load and learning achievement of students [32].…”
Section: Type Of Trainingmentioning
confidence: 99%
“…However, a large number of responses related to the integration of the technology into teaching and learning. Other studies have explored such integration; for example using digital libraries to support mobile learning activities [31] and effects of an inquiry-based mobile learning model on the cognitive load and learning achievement of students [32].…”
Section: Type Of Trainingmentioning
confidence: 99%
“…These unique features are drawing worldwide attention to the potential of m-learning in transforming the education landscape, as learners are now feasible to access, share and create knowledge anytime and anywhere (Binsaleh & Binsaleh, 2013;Fok, 2012;Hyman, Moser, & Segala, 2014;Koole, McQuilkin, & Ally, 2010). This scenario motivates learners to actively participate in their learning, impelling a change from the traditional knowledge transmission approach to a learner-centered knowledge construction paradigm (Li, Lou, Tseng, & Huang, 2013;Shih, Hwang, Chu, & Chuang, 2011). In addition, m-learning provides learners with greater flexibility by accessing just-enough, just-in-time and just-for-me contents (Peters, 2007;Rosenberg, 2001), which enhances learning effectiveness and efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…The use of mobile technologies makes it easier for students to study when and where they want (Shih et al, 2011). Mobile applications can provide students with opportunities to discover new ideas and develop deeper understanding (Khaddage and Knezek, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This study revealed that researchers are correct in that mobile technologies along with apps such as Hands-On Equations allow students to move from concrete thinking to abstract thinking, a key to algebra understanding (Walling, 2014). The use of mobile technologies makes it easier for students to study when and where they want (Shih et al, 2011), and mobile applications can provide students with opportunities to discover new ideas and develop deeper understanding of mathematical concepts (Khaddage and Knezek, 2012).…”
Section: Evaluation Of the Findingsmentioning
confidence: 99%